The Effect of Globalization on Wages in the Advanced Economies - Swagel, Phillip (IMF Working Papers; Working Paper ;, 1997)
This paper examines the effect of globalization on labor markets in the advanced economies, focusing particularly on the claim that increased economic integration has widened the gap between the wages of more skilled and less skilled workers. The broad consensus of research is that globalization, both in terms of increased trade as well as increased capital mobility and foreign direct investment, has had only a modest effect on wages. Instead, changes in technology have led to a pervasive shift in demand for labor that has favored skilled workers to the detriment of less skilled workers.